2016
DOI: 10.1007/s00705-016-3088-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of enteric viruses from diarrheic calves in Egypt

Abstract: Neonatal calf diarrhea (NCD) is a major cause of morbidity, mortality and economic losses in the beef and dairy industries. This study was conducted to investigate the existence of enteric viruses in two Egyptian farms with a history of recurrent diarrhea. Fecal samples were collected from 25 diarrheic calves. RNA was extracted and tested by reverse transcription polymerase chain reaction (RT-PCR) for the presence of rotavirus, norovirus, astrovirus, torovirus, coronavirus and bovine viral diarrhea virus. Over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 37 publications
3
36
0
Order By: Relevance
“…The results of this study confirm those of Mohamed et al [17], who found the detection rates of BNoV at 24% in Egyptian cattle as compared to 27.6% in this study. The results of both studies collectively indicate the endemic nature of BNoV infection in Egyptian cattle.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The results of this study confirm those of Mohamed et al [17], who found the detection rates of BNoV at 24% in Egyptian cattle as compared to 27.6% in this study. The results of both studies collectively indicate the endemic nature of BNoV infection in Egyptian cattle.…”
Section: Discussionsupporting
confidence: 91%
“…The results of both studies collectively indicate the endemic nature of BNoV infection in Egyptian cattle. The detected BNoV strains were genetically-related to BNoV-GIII.2 genotype (Newbury2-like), either based on BNoV-RdRp [17] or based on BNoV-VP2 (this study). BNoV-GIII.2 has a worldwide distribution, unlike BNoV-GIII.1 [23].…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…The wide host breadth of RVA strains indicated the potential of RVAs for interspecies transmission. Only one G10 strain was identified in the study, this strain is uncommon in human (Do et al, ; Luchs & Timenetsky Mdo, ) but are frequently found in animals, particularly in cattle, pigs and lambs (Ennima et al, ; Komoto et al, ; Madadgar, Nazaktabar, Keivanfar, Zahraei Salehi, & Lotfollah Zadeh, ; Mohamed, Mansour, El‐Araby, Mor, & Goyal, ; Rajendran & Kang, ). G10P[15] is an unusual combination but has previously been reported in a calf in India (Rajendran & Kang, ).…”
Section: Discussionmentioning
confidence: 95%